NARRATIVE INQUIRY: AN ADVANCED USER’S STRATEGY TO SPEAK FLUENTLY IN ENGLISH - Emeral, Emeral; Farid, Rezqan Noor (Premise: Journal of English Education and Applied Linguistics, 2024)
Speaking skills mastery is often perceived as a parameter of success in language learning. Following this situation, numerous studies and practices related to teaching speaking are continuously conducted in an attempt to best facilitate learners in developing their speaking skills. However, it catches our attention when one of our students can outperform others in speaking. This situation yields a question, “What makes him so different from the other students?”. As an attempt to elicit information about his English learning experience and strategy, especially in developing his English-speaking skills, we decided to conduct a Narrative Inquiry Research. Our research, therefore, addresses the following questions: (i) How is the advanced user’s perception of language learning? and (ii) How did the advanced user build the strategy to speak English fluently? The result of interview revealed that extramural English and some affective factors contribute to his English fluency. Investigating this phenomenon gives us insightful information, especially for language learners who want to be successful in language learning. The finding of this study is also expected to help teachers in their instructional design and practice.